Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1515/biolog-2016-0122
|View full text |Cite
|
Sign up to set email alerts
|

How dose of biochar and biochar with nitrogen can improve the parameters of soil organic matter and soil structure?

Abstract: Biochar application to agricultural soils has a significant potential to influence soil resource availability and thus crop performance. A factorial experiment investigating effects of different biochar application rates combined with nitrogen fertilizer was conducted in field conditions on a Haplic Luvisol. The aim of this study was to evaluate the effects of biochar and biochar combined with fertilization on soil organic matter and soil structure parameters. The treatments comprised combinations of biochar a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 37 publications
7
18
0
Order By: Relevance
“…For example, Burreto et al [2009] found a positive relationship between the content of organic carbon and the shares of macro-aggregates. Next, the relationship between C L and WSA ma has confirmed the results of other studies [Polláková et al 2017;Šimanský et al 2016]. An increase of macro-aggregate stability and a higher content C org and C L was also confirmed by their positive correlation with MWD W and Sw but it had a negative correlation with Kv.…”
Section: Resultssupporting
confidence: 87%
“…For example, Burreto et al [2009] found a positive relationship between the content of organic carbon and the shares of macro-aggregates. Next, the relationship between C L and WSA ma has confirmed the results of other studies [Polláková et al 2017;Šimanský et al 2016]. An increase of macro-aggregate stability and a higher content C org and C L was also confirmed by their positive correlation with MWD W and Sw but it had a negative correlation with Kv.…”
Section: Resultssupporting
confidence: 87%
“…The high MiAS value produced by BC5.0 shows that more coagulated colloids are present in BC5.0 treatment; therefore, more water stable aggregates may be formed. Several publications reported increased aggregate stability after biochar addition (Ouyang et al, 2013;Šimanský et al, 2016), which was also confirmed by the present experiment. Macroaggregate stability is also affected by plant root development over time, without the addition of any soil enhancer materials (Angers and Caron, 1998;Vergani and Graf, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Castaldi et al, 2011;Cornelissen et al, 2018). Since the biochar is alkaline, it might increase of soil pH, but this effect could be softened with adding The biochar application can be beneficial for soil pH enhancement (e. g. Chintala et al, 2013;Obia et al, 2015;Horák et al, 2017;Teutscherova et al, 2017;Šimanský et al, 2018) as confirmed by our data. As shown in Fig.…”
Section: Tablesupporting
confidence: 81%
“…According to Dai et al (2017), application of biochar, to raise soil pH, could present an acceptable solution to high soil acidity. There is a consensus that biochar application raises the pH in acidic soils Šimanský et al, 2018). Adding biochar into the soil could prove to be a valuable instrument in the efforts to increase the soil fertility and its use is deemed an important to counter the risks of soil acidification (Dai et al, 2017).…”
mentioning
confidence: 99%